Beyond deficit: 'strengths‐based approaches' in Indigenous health research. Issue 6 (19th June 2021) - Bryant, Joanne; Bolt, Reuben; Botfield, Jessica R.; Martin, Kacey; Doyle, Michael; Murphy, Dean; Graham, Simon; Newman, Christy E.; Bell, Stephen; Treloar, Carla; Browne, Annette J.; Aggleton, Peter
Abstract: Health research concerning Indigenous peoples has been strongly characterised by deficit discourse—a 'mode of thinking' that is overly focused on risk behaviours and problems. Strengths‐based approaches offer a different perspective by promoting a set of values that recognise the capacities and capabilities of Indigenous peoples. In this article, we seek to understand the conceptual basis of strengths‐based approaches as currently presented in health research. We propose that three main approaches exist: 'resilience' approaches concerned with the personal skills of individuals; 'social–ecological' approaches, which focus on the individual, community and structural aspects of a person's environment; and 'sociocultural' approaches, which view 'strengths' as social relations, collective identities and practices. We suggest that neither 'resilience' nor 'social–ecological' approaches sufficiently problematise deficit discourse because they remain largely informed by Western concepts of individualised rationality and, as a result, rest on logics that support notions of absence and deficit. In contrast, sociocultural approaches tend to view 'strengths' not as qualities possessed by individuals, but as the structure and character of social relations, collective practices and identities. As such, they are better able to capture Indigenous ways of knowing and being and provide a stronger basis on which to build meaningful interventions.